Code stroke: Multicenter experience with in‐hospital stroke alerts. Issue 3 (24th December 2014) - Cumbler, Ethan; Simpson, Jennifer
<x xml:space="preserve">Abstract</x> Between 2.2% and 17% of all strokes have symptom onset during hospitalization in a patient originally admitted for another diagnosis or procedure. A response system to rapidly evaluate inpatients with acute neurologic symptoms facilitates evaluation and treatment of stroke developing during hospitalization. The National Stroke Association implemented an in‐hospital stroke quality‐improvement initiative from July 2010 to June 2011 in 6 certified stroke centers from Michigan, South Carolina, Pennsylvania, Colorado, Washington, and North Carolina. Three hundred ninety‐three in‐hospital stroke alerts were examined over a 1‐year period. Of the alerts, 42.5% were for ischemic stroke, 8.7% probable or possible TIA, 2.8% intracranial hemorrhage, and 46.1% were stroke mimics. The most common stroke mimics were seizure, hypotension, and delirium. Participating hospitals had an alarm rate for diagnoses other than acute cerebrovascular events ranging from 28.0% to 66.7%. Of 194 in‐hospital stroke/transient ischemic attack cases, 8.2% received intravenous thrombolysis alone, 10.3% received intra‐arterial/mechanical thrombolysis alone, and 1% received both. No patient with a stroke mimic received thrombolysis. Our findings suggest that in‐hospital response teams need to be prepared to respond to a range of acute medical conditions other than ischemic stroke. Journal of Hospital Medicine 2015;10:179–183. © 2014 Society of Hospital Medicine